Assessing Brand Attitude among Urban Gen Z through Brand Awareness and Participation with Brand Pages - Indriyarti, Eko Retno; Murtiningsih, Retno Sari (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research is driven by the prevalence of TikTok among youth, particularly Generation Z, especially in urban locales where resource accessibility facilitates the platform's utilization. Conversely, the platform's prominence serves as an effective marketing tool to influence user attitudes. Consistent with this, prior research has yielded diverse outcomes regarding the development of brand views among the younger generation utilizing this platform. This study aims to evaluate the factors of brand perceptions among urban Generation Z on the TikTok platform. This quantitative study employs a questionnaire instrument including 135 Generation Z individuals in Jakarta. This study, utilizing PLS-SEM modeling and SmartPLS analytical techniques, demonstrates that active brand pages influence brand awareness but do not affect brand attitude. The findings of this study indicate that brand awareness influences brand attitude. This study effectively elucidates the mediating function of brand awareness in the relationship between active brand engagement and brand attitude.